Larval Habitats Characteristics of Mosquitoes (Diptera: Culicidae) in North-East of Iran - Aioub Sofizadeh; Seyed Hassan Moosa-Kazemi; Hossein Dehghan (Tehran University of Medical Sciences, 2017)
Background: There are unorganized, published documents about the ecology of mosquitoes (Diptera: Culicidae) in northeastern part of Iran. The purpose of this study was to determine the distribution and characteristics of larval habitats of Culicidae in Kalaleh County. Methods: Larvae were collected using dipping method and adults by human landing catch technique during April-October, 2012. Larval habitat characteristics were recorded such as vegetation status, and sunlight, water situation. Lacto-phenol and de Faure's media were used for conserving and mounting samples. Data were analyzed using SPSS statistical software, version 11.5. Results: Out of the 395 larvae collected, 332 were adult mosquitoes comprising; Culiseta, Culex, Anopheles and Ochlerotatus genera and 14 species including An. superpictus, An. maculipennis s.l., An. hyrcanus, An. psudopictus, An. claviger, Culex pipiens, Cx. theileri, Cx. perexiguus, Culiseta longiareolata, Cs. subochrea, Ochlerotatus caspius, Oc. echinus and Oc. geniculatus. Culex pipiens larvae were predominant (27.6%) and Cs. subochrea (1%) was found as the lowest species in terms of number. In the adult form, Cx. pipiens (28.9%) was predominant whereas, Cs. subochrea and Cx. perexiguus were reported to have had the lowest frequency. Conclusion: The larvae of An. superpictus and An. maculipennis species as the main vectors of malaria in north of Iran were reported in permanent habitats with clear water and vegetation, full and partial sunlight situations and muddy as well as sandy substrates that are important in larvicide application programs. Exclusive studies are necessary to diagnose An. maculipennis species complex using molecular and morphological analysis in the future.